Uniform ergodicity of nonlinear Markov operators: Dobrushin’s ergodicity coefficient for hypermatrices - Saburov, Mansoor (Academy of Sciences, Republic of Uzbekistan, 2016)
Dobrushin's ergodicity coefficient for a stochastic matrix characterizes the contraction rate of a linear Markov operator acting on a space of probability distributions equipped with the total variation norm. In this paper, we introduce Dobrushin's ergodicity coefficient for a stochastic hypermatrix which enables to provide a sufficient condition for the uniform ergodicity of nonlinear Markov operators defined by stochastic hypermatrices.